Design of IoT-Based Tomato Plant Growth Monitoring System in The Yard - Marcheriz, Isnan Nugraha; Fitriani, Endah (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The development of tomato plants to produce good fruit cannot be separated from environmental factors that affect their growth and development of tomato plants. These factors include soil moisture, soil pH, temperature, or the amount of light received by tomato plants. The need for water in tomato plants is also very important for their continued growth. Monitoring the development of tomato plants in home gardens based on IoT (Internet of Things) is a monitoring system that utilizes IoT technology to collect, transmit, and analyze data about tomato plants in real-time. In this system, sensors connected to the internet network will be installed on tomato plants to measure several parameters such as soil moisture, air temperature, light intensity, and soil nutrient / pH levels in plants. The collected data will be sent to an IoT platform that will be able to analyze the data. The results of the analysis will be used to make decisions regarding plant care, such as providing water or nutrients that the plants need to grow properly. With cameras to monitor the physical development of the plants, plant height, and fruit development. With this system, communities and farmers can grow tomato plants and can monitor and control plant conditions in real-time through smartphone applications. By utilizing IoT technology, monitoring the development of tomato plants becomes more efficient and accurate. Communities and farmers can take preventive measures to avoid plant disorders and diseases before it's too late, to increase the production and quality of crops.